The Predictive Contribution of Self-Regulated Learning and Academic Resilience to Numeracy Literacy among Fifth-Grade Elementary School Students - Lailatul Hidayati; Widyawati; Khodijatul Qubro, Nia Aulia; Dewanti, Sintha Sih; Al Kahfi, Sidik (UIN Sunan Kalijaga Yogyakarta, 2026)
This study examined: (1) the relationship between self-regulated learning and numeracy literacy, (2) the relationship between academic resilience and numeracy literacy, and (3) their joint association with numeracy literacy among fifth-grade elementary students. The novelty of this study lies in integrating self-regulated learning and academic resilience into a single model of numeracy literacy at the elementary level, whereas prior studies have mostly examined these variables separately or in secondary education contexts. Using a quantitative correlational design, data were collected from 106 fifth-grade students of SD Muhammadiyah Condongcatur selected through purposive sampling. Instruments included questionnaires on self-regulated learning and academic resilience, and a numeracy literacy test. Data were analyzed using simple and multiple linear regression. The results showed that self-regulated learning and academic resilience were significantly associated with numeracy literacy, both partially and jointly. Self-reflection was the strongest dimension of self-regulated learning, while persistence was the dominant dimension of academic resilience. These findings suggest that numeracy literacy is closely linked to students’ reflective learning regulation and academic persistence.